Impact of COVID-19 on maternal and neonatal outcomes: a systematic review and meta-analysis. (January 2021) - Di Toro, Francesca; Gjoka, Mattheus; Di Lorenzo, Giovanni; De Santo, Davide; De Seta, Francesco; Maso, Gianpaolo; Risso, Francesco Maria; Romano, Federico; Wiesenfeld, Uri; Levi-D'Ancona, Roberto; Ronfani, Luca; Ricci, Giuseppe
Abstract: Background: Previous outbreaks of severe acute respiratory syndrome coronavirus 1 (SARS-CoV-1) and Middle East respiratory syndrome coronavirus (MERS-CoV) have been associated with unfavourable pregnancy outcomes. SARS-CoV-2 belongs to the human coronavirus family, and since this infection shows a pandemic trend it will involve many pregnant women. Aims: This systematic review and meta-analysis aimed to assess the impact of coronavirus disease 19 (COVID-19) on maternal and neonatal outcomes. Sources: PubMed, EMBASE, MedRxiv, Scholar, Scopus, and Web of Science databases were searched up to 8th May 2020. Articles focusing on pregnancy and perinatal outcomes of COVID-19 were eligible. Participants were pregnant women with COVID-19. Content: The meta-analysis was conducted following the PRISMA and MOOSE reporting guidelines. Bias risk was assessed using the Joanna Briggs Institute (JBI) manual. The protocol was registered with PROSPERO (CRD42042020184752). Twenty-four articles, including 1100 pregnancies, were selected. The pooled prevalence of pneumonia was 89% (95%CI 70–100), while the prevalence of women admitted to the intensive care unit was 8% (95%CI 1–20). Three stillbirths and five maternal deaths were reported. A pooled prevalence of 85% (95%CI 72–94) was observed for caesarean deliveries. There were three neonatal deaths. The prevalence of COVID-19-related admission to the neonatal intensive care unit was 2% (95%CI 0–6). Nineteen out of 444 neonates were positive for SARS-CoV-2 RNA at birth. Elevated levels of IgM and IgG Serum antibodies were reported in one case, but negative swab. Implications: Although adverse outcomes such as ICU admission or patient death can occur, the clinical course of COVID-19 in most women is not severe, and the infection does not significantly influence the pregnancy. A high caesarean delivery rate is reported, but there is no clinical evidence supporting this mode of delivery. Indeed, in most cases the disease does not threaten the mother, and vertical transmission has not been clearly demonstrated. Therefore, COVID-19 should not be considered as an indication for elective caesarean section.